ANALISIS PENENTUAN MUTU AIR BEBERAPA SUNGAI DI JAWA TENGAH DENGAN METODE STORET DAN INDEKS PENCEMARAN - Huboyo, Haryono Setiyo; Nugraha, Winardi Dwi; Indah, Rahmah (Universitas Diponegoro, 2009)
There are some river basin in Central Java, such as Gung River Basin, Serayu River Basin and Garang River Basin. Many sector that are dependable on the river resources, while on the hand the quality of the river is decreasing because of the waste water pollutant produced by many human or industrial activities. Therefore, proposal study of water class determination can be done by 2 methods according to Environmental Ministry Decision No. 115 year 2003 about Water Quality Status Determination Handbook, which are STORET and Pollution Index (PI). Using those two methods will be determined the real water class through comparison between water quality parameter with defined standard according to PP No. 82 year 2001. The usage of these 2 methods often resulting in different output, because of the difference of equal weight from each parameter and the existence constanta of P at Pollution Index (PI) which not clear relevancy.